Screening instruments for monitoring market power in wholesale electricity markets: Lessons from applications in Germany - Marc Bataille; Alexander Steinmetz; Susanne Thorwarth (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2014)
While liberalization in energy markets has been a widely successful process all over the world, incumbents often still hold a dominant position. Thus, electricity wholesale markets are subject to market surveillance. Nevertheless, consolidated findings on abusive practices of market power and their cause and effect in wholesale electricity markets are scarce and non-controversial market monitoring practices fail to exist. Our application of the established measure of market concentration RSI shows that it serves as a decent indicator for the rents that can be gained in the market but also reveals considerable weaknesses of the RSI. Therefore, we propose and apply the "Return on Withholding Capacity Index" (RWC) representing a measure of the firms' incentive of withholding capacity as a complementary index to the RSI.
Keywords: L11; L43; L94; K23; C13; 330; Market Power; Electric Power Markets; Measurement